Measuring real exchange rate misalignment: an industry-level analysis of Pakistan using ARDL approach - Aqsa Shaukat; Eatzaz Ahmad; Waseem Shahid Malik (Cogent Business & Management, 2022)
Having an exchange rate close to its equilibrium is critical for foreign investors and policymakers during times of macroeconomic instability. This study measures the real exchange rate (RER) misalignment in eight Pakistani manufacturing industries from January 2002 to June 2020. The ARDL approach is used to examine the long-run relationship between the RER and its fundamentals in each industry. The findings show that government spending and interest rates significantly explain RER at the aggregate and industrial levels. Furthermore, the misalignment of RER varies significantly across industries. Some industries have highly misaligned RER, while others have close to zero misalignments. These findings can assist us in making fiscal policy and competitive devaluation decisions to improve the trade deficit.
Keywords: 650; Pakistan; ARDL; industries; Real exchange rate misalignment